AGRONOMIC CHARACTERS OF DROUGHT-TOLERANT SOYBEANS AT THE REPRODUCTIVE STAGE - Adie, M. Muchlish; Krisnawati, Ayda (Research Center for Biology-Indonesian Institute of Sciences, 2019)
In Indonesia, soybeans are typically cultivated during the dry season, thus making it prone to drought stress in the reproductive stage. The objective of the research was to characterize the agronomic characters of several soybean genotypes which were tolerant to drought at the reproductive stage. A total of 19 soybean genotypes were evaluated for its agronomic characters and tolerance to drought stress in Probolinggo (East Java, Indonesia) during the dry season (June ? September). The research was arranged in a randomized block design with four replicates. Soybean cultivars were sown at two separate experiments, normal/optimal (plants were irrigated during the growth period) and stress (plants were irrigated up to 40 days after planting) conditions. Drought stress during the reproductive stage did not affect the characters of plant height, the number of branches per plant, the number of nodes per plant, and the number of pods per plant. Meanwhile, the number of empty pod, seed weight per plant, and seed yield were significantly affected. There were two genotypes which were identified as the tolerant genotypes to drought stress at the reproductive stage, i.e. MDT15-6-11 and MDT15-W-3034. The agronomic characters of MDT15-6-11 were showed as having a low percentage of yield reduction, hence it was able to mantain its high yield. The MDT15-W-3034 was identified as drought-tolerant due to the slow wilting, high plant character, a slow vegetative phase, and high yields. The genotypes obtained from this study could be recommended to be released as new soybean drought-tolerant varieties due to its high yield and tolerant to drought stress. Those genotypes could also be used as gene donors for soybean improvement to drought stress at the reproductive stage.